Comparative study of enzymatic activities of new KatG mutants from low- and high-level isoniazid-resistant clinical isolates of Mycobacterium tuberculosis. (September 2016) - Brossier, Florence; Boudinet, Marlène; Jarlier, Vincent; Petrella, Stéphanie; Sougakoff, Wladimir
Summary: Resistance to isoniazid (INH-R) in Mycobacterium tuberculosis is mainly due to mutations at position 315 (S315T) of the catalase-peroxidase KatG. We identified 16 mutations (including 13 biochemically uncharacterized mutations) in KatG from INH-R clinical isolates of M. tuberculosis showing mutations other than S315T. The KatG enzymatic activities (catalase, peroxidase, free radical production and isonicotinoyl-NAD formation) of wild-type KatG and the 16 mutants were determined and correlated to their spatial location in a KatG model structure. Of all mutations studied, H270R, which conferred a high level of INH-R and results in the disruption of a coordination bond with the heme, caused complete loss of all enzymatic KatG activities. The mutants generally associated with a very high level of INH-R were all characterized by a drastic reduction in catalase activity and a marked decrease in INH activation activities. One mutant, A162E, displayed a behavior similar to S315T, i.e. a moderate decrease in catalase activity and a drastic decrease in the formation of the radical form of INH. Finally, the mutants associated with a low level of INH-R showed a moderate reduction in the four catalytic activities, likely stemming from an overall alteration of the folding and/or stability of the KatG protein.